PERAN ORANG TUA TERHADAP PERILAKU ANAK REMAJA MENGONSUMSI TUAK DI DESA BAKAL JULU KABUPATEN DAIRI SUMATERA UTARA (Program Studi Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Udayana, 2022)
Nowadays, adolecents are lacking of self-control and act on their own pathways without considering other people around them. Many youngsters in my village, Bakal Julu drink Tuak (popular traditional alcoholic drink) at kode (house cafe/warung) during day time and even night. Some of these youngsters are mostly schoolers. Oftentimes, parents ignore them as if they seem not care and let them do it repeatedly by saying too tired of reminding them not to but they keep on drinking it purposely. This research is aimed to describe and clearly explain the factors of why these youngsters drink tuak and parents' role in preventing them to not drink it. This research is conducted using qualitative method with descriptive explanatory way of design. This reasearch was supported by a popular American sociologist Travis Hirschi on his theory